Pengembangan Sistem Pertanian Terpadu Berbasis Potensi Lokal di Desa Dayun Melalui Kolaborasi Mahasiswa Kkn dan Pemerintah Desa - Nurul Fadillah; Sukamarriko Andrikasmi; Laila Fitria; Abzar Pratama; Al Fazri Efendi; M. Adib Agusri; Fransiska Dwiana Simanungkalit; Luthfiyah Dwijayanti; Astri Monica Lumbantoruan; Husnaini Fadyah; Ct Sarach; Risky Mardiansyah; Arif Syahbani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Developing an integrated agricultural system based on local potential is an effective strategy for addressing the challenges of efficiency, sustainability, and food security in rural areas. Dayun Village in Siak Regency boasts diverse potential, including underutilized agricultural land, fish ponds, cattle ranches, and hydroponic installations. Through the University of Riau's Community Service Program (KKN), the village government and community collaborated to design and implement an integrated agricultural system that integrates the agriculture, fisheries, livestock, and horticulture sectors. The approach used was participatory and transformative, starting with identifying potential and needs, planning activities, implementing activities such as spreading gourami seeds, planting productive trees (MPTS), and reactivating hydroponic installations, and conducting community survey-based evaluations. The results of the activities demonstrated increased community participation, understanding of the integrated agricultural system, and improved ecological and economic awareness. This activity demonstrates that cross-sector collaboration and optimizing local potential can strengthen the village economy and sustainably secure food security.